Evolution analysis of GH3 gene family in five Rosaceae species and FaGH3.17, FaGH3.18 improve drought tolerance in transgenic Arabidopsis - Lili Guo; Shixiong Lu; Huimin Gou; Jiaxuan Ren; Juanbo Yang; Baozhen Zeng; Juan Mao; Baihong Chen (BMC Plant Biology)
Abstract Background Gretchen Hagen 3 (GH3), one of the important auxin-responsive gene families, plays essential roles in plant growth, development process, and stress response by regulating hormone homeostasis. However, the evolutionary analysis of the GH3 gene family in Rosaceae species has not been well-studied and the specifc functions of Fragaria ananassa are not well-documented. Results In the current study, 64 members of the GH3 family genes were identifed from five Rosaceae species and divided into 8 groups. According to the comprehensive analysis of evolutionary relationship, collinearity, selection pressure and codon bias, the GH3 gene family was found to be highly conserved across these Rosaceae species, suggesting that purifying selection was a significant force in the evolution of GH3 genes, and the expansion of the GH3 gene family in Rosaceae species might be attributed to fragment duplication. Meanwhile, the codon bias of GH3s in subfamily G and K showed a relatively strong codon bias. Significantly, both FaGH3.17 and FaGH3.18 were localized in the cytoplasm and nucleus. Additionally, compared with the wild type (WT), the malondialdehyde (MDA) content and relative conductivity of FaGH3.17 and FaGH3.18 transgenic Arabidopsis were decreased, while the superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) activities were increased under drought stress. The above results indicate that overexpression of FaGH3.17 and FaGH3.18 signifcantly enhanced the tolerance to drought in transgenic Arabidopsis. Conclusions The study provides crucial insights into the evolution of the GH3 gene family in Rosaceae species and provides a theoretical basis for further investigation on the function of FaGH3s.